(NiZBRANNYE PROIZWEDENIQ (B/ s - (NpASTERNAK(B, (NbORIS lEONIDOWI^s ((NmOSKWA(B: s (NpANORAMA(B, s, 1991)
(Nw KNIGU b(B. (Nl(B. (NpASTERNAKA WO[LI LU^[IE STIHOTWORENIQ PO\TA(B, (NFRAGMENTY IZ PO\MY (B"(NdEWQTXSOT PQTYJ GOD(B", (NA TAKVE ROMAN (B"(NdOKTOR vIWAGO(B".s
rus
Keywords: (NsTIHOTWORENIQs; (NrOMANs